PINARBAŞI-SARIZ-TOMARZA AVŞAR AĞITLARI - ALTINKAYNAK, ERDOĞAN (Fırat Üniveristesi, 1997)
[Abstract Not Available]
The mourning songs of Pinarbasi-Sariz-Tomarza Avsar
Keywords: Halk Bilimi (Folklor); Folklore